The Context of Using Code Switching between Students and Lecturers at Islamic Education Management Study Program: A Sociolinguistic Study - Lela Susanty; Jefriyanto Saud; Ahmad Munawir; Julhadi; Faizin (RETORIKA: Jurnal Ilmu Bahasa, 2023)
In general, the use of code switching often occurs among the community. But in this case, the context of the use of code switching used by students and lecturers in the Islamic education management study program has characteristics and uniqueness that can attract someone's attention. This study aims to describe the form and context of the use of code switching between students and lecturers in the Islamic education management study program. The method used in this study is a descriptive qualitative research. The data in this study are sentences containing code-switching utterances, while the data source is the utterances of students and lecturers in the Islamic education management study program. The data were obtained from interviews with students and lecturers by voice recording and field note-taking. In addition, the researchers also used the reflective-introspective method. The collected data were then transcribed into a written form of orthographic transcription. The method applied for analyzing the data is equivalent and distributional method. Meanwhile, the methods used for displaying the results of data analysis are informal and formal steps. The results showed that there were 3 forms of code switching in speech between students and lecturers, namely 1) code switching from EL to IL ; 2) code switching from ML to IL; and 3) Code switching from AL to IL. The context of its use is motivated by multilingual factors, speakers, speech partners, topics of conversation, atmosphere of conversation, weak language, lack of vocabulary, just prestigious, and wanting to make it easier for the speech partner to understand the message conveyed.